(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Beta Thalassemia Major is a major health problem and approximately ten thousand thalassemic children are registered in different thalassemia centers in Pakistan. Clinical severity and transfusion frequency is varied person to person. Elevated Hemoglobin F (HbF) in thalassemia patients is considered less clinical severe then low level. Objectives: Present study is designed to evaluate correlation between HbF level with disease severity. To determine correlation of HbF with Hematological parameters in Beta Thalassemia major patients Material and method: It were descriptive cross-sectional study conducted at institute of paramedical sciences and Peshawar institute of medical sciences, Peshawar. Study duration was from 24 Jun 2022 to 8 Dec 2022. Co-inheritance of β Thalassemia major with other hemoglobinopathy were excluded. Total of 101 thalassemia Patients history, demographic information, and clinical detail were obtained under the supervision of clinical Hematologist. Two mL of venous blood were taken in EDTA vacutainer tube for complete blood count and HbF level, 2 mL blood were also taken in heparin vacutainer tube for serum ferritin level. CBC was performed on automated hematology analyzer (XN-1000, Sysmex, Japan) and hemoglobin electrophoresis was performed on Sebia capillary 2 analyzers. Serum ferritin was performed on automated biochemistry analyzer (Cobas e622 Roch Germany). Results: Out of 101 thalassemia patients 55(55.5%) were male and 46(46.5%) were female with mean age 8.73 (±6.71) with mean age at 1st transfusion of study population were 19.04(±23.96) month with maximum age at 1st transfusion were 144 months. The mean Hb of the studied population were 6.731313 (±2.0306) g/dl with maximum Hb were 13.000 g/dl with the mean RBC of the studied population were 2.74273 (±1.17436) (m/ ul) with maximum RBC, s was 9.300 m/ ul.). The mean Ferritin of the studied population were 3538.85(±2758.599) ng/mL with maximum ferritin were 15536 ng/mL. The mean HbA2 of the studied population were 3.310101 (±5.18157) % with maximum HbA2 were 51.0000 %. The mean HbF of the studied population were 76.111111 (±28.3777) % with maximum HbF were 99.0000 %Conclusion: In the present study, concluded that in patients with β thalassemia major, there is significant correlation between HbF and HbA2 and also HbA1 in hematological parameters so there is increasement of severity with level of HbF and HbA2 and also there is significant correlation between HbA2 and HbA1.But no correlation was found between HbF and HbA2 in clinical parameter.